The Effect of Mindfulness and Spiritual Combination Breathing Exercises towards Anxiety, Depression and Blood Pressure of Ischemic Stroke Patients - Anie Tri Indiartinie; Eppy Setiyowati; Mulyadi (Journal Of Nursing Practice, 2024)
Background: Ischemic stroke causes serious ongoing problems in the lives of sufferers, including biological, psychological and spiritual changes so that comprehensive and multidisciplinary nursing care is necessary. Purpose: The purpose of this research is to analyze the effect of Mindfulness and Spiritual Combination Breathing Exercises towards anxiety, depression and blood pressure of ischemic stroke patients. Methods: This research is a quantitative research that uses a quasy experimental research design with a pretest - posttest control group design approach. The population of all ischemic stroke patients at RSAU dr. M.Munir Lanud Abdulrachman Saleh Malang as many as 108 people. The sample size is 50 respondents. The sampling technique is purposive sampling. The intervention group was given a combination of Mindfulness and SpiritualityBreathing Exerciseswithin 10-15 minutes 2 times a day for 5 days and the control group was given intervention according to hospital standards. Analysis used the Manova test with a significant p value <0.05. Results: The results of the study using the Manova test showed that there was a significant effect between anxiety, depression and blood pressure after giving the Combination of Spiritual Mindfulness and Breathing Exercise sshowed that p value = 0.000, with the highest partial Eta Squared value of 0.643 anxiety followed by 0.579 depression and 0.263 blood pressure. Conclusion: A combination of Spiritual Mindfulness and Breathing Exercises effectively reduce the level of anxiety, depression and blood pressure of ischemic stroke patients.